Hubungan antara Lingkungan Fisik Sekolah dengan Motivasi Belajar Siswa di Sekolah XWZ - Yunus, Cantika Wulandari; Ohoirat, Andito Zeth (ARZUSIN, 2025)
This research aims to determine: 1) The relationship between the physical environment of the school and student learning motivation. The population of this study was XWZ State Junior High School students, totaling 256 students determined using a cluster random sampling technique with a total research sample of 64 students. The measuring instruments used are the learning motivation scale and the school physical environment scale. and learning motivation arranged according to the Likert Scale method. The first and second hypothesis analysis techniques use simple regression techniques, while the third hypothesis uses multiple regression analysis techniques. The first hypothesis was proven to have a positive relationship between the school's physical environment and learning motivation from an F value of 26.745 and a p value of <0.001 (p<0.05). The effective contribution of the school's physical environment to collective learning motivation is 55.77% while the remaining 44.23% is influenced by other factors not examined in this research.